Hard input, soft management and student engagement: How institutional actions promote innovation ability and academic performance among top innovative talent - Tianbao Zhang; Weihai Huang; Zhimin Liu (PLoS ONE, 2025)
The training and cultivation of innovative talent, especially top-quality talent, cannot be explained fully by reference to a simple linear input‒output model. Research that can open the “black box” that characterizes this process has important theoretical and practical significance with respect to efforts to promote the development of high-quality education. By reference to a sample consisting of 1,500 graduating doctoral students who participated in a national stratified sampling survey in China, we develop a structural equation model with the goal of investigating the different roles played by the hard inputs and soft management employed by institutions in the task of cultivating top-quality innovative doctoral students as well as the specific paths associated with this influence. Our analysis reveals that promoting learning initiative among doctoral students and regulating their level of scientific research engagement are important ways in which various institutional inputs, especially soft management measures, can affect the intrinsic innovation ability of doctoral students, whereas efforts to encourage doctoral students to pursue top-quality academic achievements on the basis of their acquisition of relevant capabilities are related mainly to the hard inputs provided by institutions.